2022
DOI: 10.1021/acs.langmuir.1c03205
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Adsorption Kinetics of Surfactants at the Water–Oil Interface via Grand-Canonical Molecular Dynamics Simulations

Abstract: It is well-known that surfactants tend to aggregate into clusters or micelles in aqueous solutions due to their special structures, and it is difficult for the surfactant molecules involved in the aggregation to move spontaneously to the oil−water interface. In this article, we developed a new grand-canonical molecular dynamics (GCMD) model to predict the saturated adsorption amount of surfactant with constant concentration of surfactant molecules in the bulk phase, which can prevent surfactants aggregating in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 78 publications
0
6
0
1
Order By: Relevance
“…Phan et al established a new model without using the Gibbs equation to quantify the adsorption of cationic surfactants (C 14 TAB and C 16 TAB) at the air–water interface and validated this model by MD simulations. Yang et al, via grand canonical MD simulations, investigated the saturated adsorption of SDS at the oil–water interface. During the simulation process, SDS molecules were gradually released to the interface until the adsorption and desorption at the interface reached equilibrium, which indicates that the interface was saturated.…”
Section: Introductionmentioning
confidence: 99%
“…Phan et al established a new model without using the Gibbs equation to quantify the adsorption of cationic surfactants (C 14 TAB and C 16 TAB) at the air–water interface and validated this model by MD simulations. Yang et al, via grand canonical MD simulations, investigated the saturated adsorption of SDS at the oil–water interface. During the simulation process, SDS molecules were gradually released to the interface until the adsorption and desorption at the interface reached equilibrium, which indicates that the interface was saturated.…”
Section: Introductionmentioning
confidence: 99%
“…Simulating the behavior of more SDS molecules within a limited simulation system can provide more statistical samples for analysis, favoring the reduction of errors. Therefore, each SDS molecule was set with an initial occupied surface area of 0.49 nm 2 (slightly larger than the minimum occupied surface area of a single SDS molecule) 55 and uniformly aligned perpendicular to the x-y plane. For each surfactant molecular layer, there are 36 SDS molecules.…”
Section: Methodsmentioning
confidence: 99%
“…Besides the experimental investigation, the theoretical calculation of molecular simulations (MS) can be utilized as an available method to provide direct observations for interfacial phenomenon. A series of literature have been reported for oil− water interfacial adsorption investigation of surfactants, 30 polymers, 31 and polycyclic aromatic compounds. 32 These results indicated that the intrinsic characteristics of interfacial adsorption behavior can be deeply interpreted and supplementary explicated from microscopic aspects by molecular simulation.…”
Section: Introductionmentioning
confidence: 99%